Perbaikan Ulkus Diabetik Dengan Penerapan Latihan Range Of Motion Ekstremitas Bawah Pada Diabetes Tipe 2 - Shanty Chloranyta; Eko Junaidi; Jupri Kartono (Madago Nursing Journal, 2022)
Diabetic ulcers are one of the chronic complications of type 2 diabetes due to chronic hyperglycemia resulting in impaired perfusion and neuropathy. Range of motion exercises in lower extremities improve peripheral perfusion with the aim of facilitating the diffusion of oxygen and adequate supply of nutrients to the ulcer area. The research objectives were identified and analyzed for diabetic improvement in the application of lower extremity range of motion exercises. Case study research design, 2 research subjects, at the Wound Clinic Diabetes Center Bandar Lampung for 2 weeks. The results of the study before the lower extremity range of motion of the degree of diabetes of the two respondents scored 2, after the range of motion of the lower extremity of the degree of diabetes both respondents scored 1. The conclusion of this study showed that lower extremity range of motion exercises can improve the repair of diabetic ulcers in type II diabetes patients. Lower extremity range of motion exercise can be one of the independent interventions carried out for the treatment of diabetic foot ulcers in type 2 diabetes.